A systematic literature review on Safe Routes To School (SRTS) program and factors influencing travel mode choice to school / Nur Shaffiqa Muhammad Soffian, Amelia Ahmad and Norsyazlin Mohd Rosli - Muhammad Soffian, Nur Shaffiqa; Ahmad, Amelia; Mohd Rosli, Norsyazlin (2022)
Children is the most exposed road users where their most frequent main option modes of transport are walking and cycling. This paper attempts to establish a systematic review of existing literature on Safe Routes to School (SRTS) program. This study examines several aspects of literature review which include the issues prior to the existence of the Safe Routes to School (SRTS) Program and factors that influence travel mode choice among parents in commuting their children to school. The outcome of this article is to provide direction for future studies. It is necessary to address parent's concern in transporting their children to school. This paper could be very helpful for researchers, policy makers and whoever interested in making sustainable cities and communities in accordance with the principles of Sustainable Development Goals.